Caveolae and caveolin-1 in human term villous trophoblast. - Linton, E; Rodriguez-Linares, B; Rashid-Doubell, F; Ferguson, D; Redman, C (2003)
Caveolae are flask-shaped invaginations of the plasma membrane found in many cell types, particularly endothelium. A major structural component is the membrane protein caveolin-1 which associates with numerous signalling molecules, including endothelial nitric oxide (eNOS). Caveolin-1, which co-immunoprecipitates with eNOS in preparations from endothelial cells, regulates eNOS activity, holding it inactive. Controversy now exists regarding the presence of caveolae and caveolin-1 in trophoblasts, hence this study was carried out to examine whether the high levels of eNOS expressed in human syncytiotrophoblast are associated with caveolin-1, and to find out if caveolae are present in villous cytotrophoblasts and syncytiotrophoblast. Immunohistochemistry of term placentae revealed only weak labelling for caveolin-1 in the syncytiotrophoblast although the endothelium of the terminal villus vessels stained strongly. By electron microscopy, numerous caveolae were identified in the villus capillary endothelium but were extremely rare in the syncytium. Caveolin-1 staining was extensive in purified, isolated term villous cytotrophoblasts, with the purity of these cytokeratin positive cells confirmed by cytospin analysis and flow cytometry. Caveolae were clearly demonstrated in ultrastructural sections of the purified cytotrophoblasts. The time course of expression of caveolin-1 and eNOS during differentiation of villous cytotrophoblast into syncytiotrophoblast in culture was studied. Western analysis showed that caveolin-1 expression evident in day 1 whole cell lysates decreased at day 3 when the cells had syncytialized and declined further by day 6, while the levels of actin (control) remained high. eNOS expression in the same samples followed a different pattern, with the low levels in day 1 cells increasing substantially by 3 days in culture, subsiding again by day 6. eNOS association with caveolin-1 in day 1 and day 3 trophoblast cultures was evidenced by the demonstration that eNOS co-immunoprecipitates with caveolin-1 and vice versa. We conclude that human villous cytotrophoblasts express caveolin-1, which assembles into caveolae. Differentiation into syncytium results in a decrease, but not disappearance, of expression of caveolin-1 and a marked reduction of the caveolae.